2022
DOI: 10.3390/microorganisms10122441
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Thermophilic Bacteria and Investigation of Their Microplastic Degradation Ability Using Polyethylene Polymers

Abstract: Microplastics (MPs) pose potential public health challenges because of their widespread occurrences in all environmental compartments. While most studies have focused on the occurrence fate of microplastics in wastewater treatment systems, the biodegradation of microplastics in wastewater is generally little understood. Therefore, we used two Gram-positive and thermophilic bacteria, called strain ST3 and ST6, which were identified by morphological, biochemical, physiological, and molecular analyses, to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…A few studies have shown that the MP surface becomes rougher following biofilm formation. For example, Özdemir et al ( 2022 ) reported holes, grooves, and cracks in PE MPs following 10 days of incubation with thermophilic bacteria. Auta et al ( 2017 ) also showed changes in surface roughness in PE, PET, PP, and PS after biofilm formation.…”
Section: Physicochemical Changes Of Mps Induced By Biofilm Formationmentioning
confidence: 99%
“…A few studies have shown that the MP surface becomes rougher following biofilm formation. For example, Özdemir et al ( 2022 ) reported holes, grooves, and cracks in PE MPs following 10 days of incubation with thermophilic bacteria. Auta et al ( 2017 ) also showed changes in surface roughness in PE, PET, PP, and PS after biofilm formation.…”
Section: Physicochemical Changes Of Mps Induced By Biofilm Formationmentioning
confidence: 99%